THE RELATIONS OF RELIGION AND ETHNICITY OF URBAN COMMUNITIES IN SURABAYA - Basyir, Kunawi (State Islamic University North Sumatra, 2020)
Abstract: The phenomenon of social life related to religion and ethnicity of urban communities in Surabaya has been and is becoming a special concern for the government of Surabaya and academicians Because, the metropolitan city (Surabaya) which has various types of differences in religion, ethnicity, and culture of ethnic communities (Javanese, Madurese, Chinese, Arabic) has provided its color of in-depth study and research. This article will describe the results of studies and research with the title